I'm getting a couple of different answers from different sources, so I'd like to verify something.

I misplaced my original notes from my prof, but working from memory I have the following:

\begin{align} \int\csc(x)\ dx&=\int\csc(x)\left(\frac{\csc(x)-\cot(x)}{\csc(x)-\cot(x)}\right)\ dx\\ &=\int\frac{\csc^{2}(x)-\csc(x)\cot(x)}{\csc(x)-\cot(x)}\ dx\\ &=\int\frac{1}{u}\ du\\ &=\ln|u|+C\\ &=\ln|\csc(x)-\cot(x)|+C \end{align}

This looks proper when I trace it, but wolfram alpha is saying that the answer should be


Sadly, it doesn't provide a step-by-step. It just says that's the answer.

So which is it? Or are they both equivalent? I've never been great with the laws of logarithms.


Start with the identity

$$(\csc x-\cot x)(\csc x+\cot x)=\csc^2x-\cot^2x=1\;;$$

this implies that

$$|\csc x-\cot x|\cdot|\csc x+\cot x|=|\csc^2x-\cot^2x|=1\;.$$

Now use the fact that if $a,b>0$ and $ab=1$, then $\ln a+\ln b=\ln 1=0$, so $\ln a=-\ln b$ to conclude that

$$\ln|\csc x-\cot x|=-\ln|\csc x+\cot x|\;,$$

and the two answers are the same.

  • $\begingroup$ That's quite interesting - I never would have known that. $\endgroup$ – agent154 Mar 10 '13 at 0:02
  • 2
    $\begingroup$ That's pretty sophisticated logic, I have to admit) $\endgroup$ – Alex Mar 10 '13 at 1:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.